Recent advances in the application of isoindigo derivatives in materials chemistry - Bogdanov, Andrei V.; Mironov, Vladimir F. (Beilstein Journal of Organic Chemistry, 2021)
In this review, the data on the application of isoindigo derivatives in the chemistry of functional materials are analyzed and summarized. These bisheterocycles can be used in the creation of organic solar cells, sensors, lithium ion batteries as well as in OFET and OLED technologies. The potentials of the use of polymer structures based on isoindigo as photoactive component in the photoelectrochemical reduction of water, as matrix for MALDI spectrometry and in photothermal cancer therapy are also shown. Data published over the past 5 years, including works published at the beginning of 2021, are given.
Keywords: isoindigo; OFET; photoactive polymers; photovoltaics; solar cells